2017
DOI: 10.15517/ijds.v0i0.28952
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microleakage by Gas Permeability and Marginal Adaptation of MTA and Biodentine™ Apical Plugs: In Vitro Study

Abstract: The endodontic treatment of teeth with incomplete development is always a complex task. Nowadays, biomaterials such as bioceramics offers promising clinical evidence that supports its use. However, the standardization of its use for apexification purpose still needs a deeper understanding of the materials’ behavior. The aim of this investigation was to evaluate the marginal adaptability and microleakage by gas permeability of MTA and Biodentine™ apical plugs in an in vitro model. Materials and methods: Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Although MTA showed, to some extent, better adaptation than Biodentine, they did not differ significantly. This was in agreement with Mohan et al, Brenes-Valverde et al, and Juez et al [ 37 , 38 , 49 ], who found that MTA and Biodentine showed similar adaptation. The high sealing ability of MTA is probably due to the setting expansion with time, which likely leads to the closure of the gaps inside the cavity [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although MTA showed, to some extent, better adaptation than Biodentine, they did not differ significantly. This was in agreement with Mohan et al, Brenes-Valverde et al, and Juez et al [ 37 , 38 , 49 ], who found that MTA and Biodentine showed similar adaptation. The high sealing ability of MTA is probably due to the setting expansion with time, which likely leads to the closure of the gaps inside the cavity [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have addressed the internal adaptation of new pulp capping materials (TheraCal and Biodentine), and they reported a dialectical outcome [ 10 , 37 , 38 ]. Furthermore, no research has been performed to correlate OCT with Micro-CT for the evaluation of internal adaptation of pulp capping materials.…”
Section: Introductionmentioning
confidence: 99%
“…15 The main objective of all endodontic procedures is to obtain a hermetic seal between the periodontium and root canal foramina. 16 The apical plug method is regarded as the golden standard for apexification as it is a single visit technique, has less need for patient's cooperation and gives satisfactory results 17 therefore, MTA and Biodentine are recommended options to perform apexification plugs. 18 In-vitro experimental study should be performed before embarking on to in-vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Also, in vitro evaluations consistently report that BD and MTA can increase the cell proliferation and biomineralization of dental pulp cells. [6][7][8][9][10][11][12][13][14][15][16][17] In addition, the cells' features are important to consider; previously reported data showed that GF have distinct functional activities during the regeneration and repair of periodontal tissues, and that PF can differentiate to diverse cell types, including osteoblast, depending on the external stimuli. [15][16][17][18] In the present study, we used an in vitro model to compare the effects of MTA and BD in GF, and compared the results with the effects on PF.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] It has been suggested that MTA and BD release toxic substances before complete setting, and that the toxicity disappears with time. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In this regard, few studies have evaluated the cytotoxic effects of bioactive endodontic cements on primary cell lines at 168 hours.…”
Section: Discussionmentioning
confidence: 99%